A new p-dimethylaminocinnamaldehyde reagent formulation for the photoluminescence detection of latent fingermarks on paper - Fritz, Patrick; Van Bronswijk, Wilhelm; Lewis, Simon (Elsevier Ireland Ltd, 2015)
Dimethylaminocinnamaldehyde was re-evaluated as a wet contact reagent for the treatment of latent fingermarks on porous substrates. A new formulation (consisting of 0.028 g p-dimethylaminocinna- maldehyde, 0.84 mL glacial acetic acid, 6.2 mL ethyl acetate and 0.993 L 40–60 8C petroleum spirits) provides quick, sensitive and robust luminescent ridge detail within 3 h of treatment on both plain and thermal paper. Comparisons to existing formulations indicate improved visualisation and/or a more efficient process.